POTENCIAL ENERGÉTICO DE RECUPERAÇÃO DE ALUMÍNIO DO COMPÓSITO PEBD/Al VIA PIRÓLISE: SEGREGAÇÃO EM LEITO DE JORRO - Mantegazini, Diunay Zuliani (2020)
Among the carton packages waste recovery processes, pyrolysis is reported as a sustainable, clean and innovative technology. Its use makes it possible to obtain products with high added value, such as paraffinic oils and aluminum ingots, in addition to co